ANALISIS IMPLEMENTASI KEBIJAKAN PENGENDALIAN PEMBUANGAN LIMBAH CAIR DOMESTIK KE BADAN AIR PENERIMA DI KABUPATEN PURWAKARTA - Futiha Nazar; Sutarto Mochtar; Ely Sufianti; Endang Wirjatmitrilestari; Edah Jubaedah (Program Magister Ilmu Administrasi dan Kebijakan Publik, Pascasarjana, Universitas Pasundan, 2021)
The implementation of the domestic liquid waste disposal control policy in Purwakarta Regency has not been implemented because there are no regulations regarding its management. So far, domestic wastewater is discharged directly into drainage channels / rivers due to the unavailability of facilities and infrastructure for domestic wastewater management, lack of public understanding of the impact of domestic wastewater on water pollution. In addition, there are no operational level regulations regarding the implementation of domestic wastewater management policies. The method used is a qualitative approach with information from policy implementers at the Environmental Agency and related sub-district. Analysis of policy implementation uses the George C. Edward III approach which includes communication, resources, dispositions and bureaucratic structures. The results showed that in order to solve the problem of implementing the domestic liquid waste disposal control policy, the Purwakarta Regency Government needs to carry out several actions in controlling domestic liquid waste disposal pollution to receiving water bodies. The steps that can be taken are optimizing the performance of limited human resources, provision of a budget, and cooperation between the government, the private sector and the community. Policy implementation can be carried out if Purwakarta Regency already has references including inventory data and identification of sources of domestic liquid waste pollutants, Standard Operational Procedure (SOP) for Domestic Wastewater Disposal Control, and regent regulations on domestic liquid waste management.